Rumination, Posttraumatic Stress Disorder Symptoms, and Posttraumatic Growth Among Wenchuan Earthquake Adult Survivors: A Developmental Perspective - Xu, Wenjian; Feng, Chengxiang; Tang, Wanjie; Yang, Yifan (Frontiers in Public Health, 2022)
This study examined the long-term effects of the Wenchuan earthquake among adult survivors. Specifically, it explored the role of perceived social support (PSS) in the relationship between rumination and posttraumatic growth (PTG) and posttraumatic stress disorder (PTSD) symptoms. Data were collected from March to July 2020 using a youth survivor sample (n = 476) of the 2008 Wenchuan earthquake. Participants were divided into three groups depending on their age when the quake occurred: 6–11 years (n = 227), 12–15 years (n = 83), 16–19 years (n = 166). The results indicated that long-term PTG and PTSD symptom levels varied by age group. Both intrusive and deliberate ruminations had a significant effect on PTG as well as PTSD symptoms. PSS played a mediating role between rumination and PTG, and the mediation mechanisms varied by age group (developmental stages). Moderated analyses revealed that PSS from significant others significantly buffered the indirect effect of rumination on PTSD symptoms. Our findings demonstrated the universal nature of traumatic events encountered during childhood and adolescence development and underscore the importance of examining the developmental context of PTG in investigations on traumatic experiences and their consequences.